The girl who fell beneath the sea - Oh, Axie (Feiwel and Friends, an imprint of Macmillan Publishing Group, LLC, 2022)
In this retelling of the Korean legend The tale of Shim Cheong, sixteen-year-old Mina is swept away to the Spirit Realm, where, assisted by a motley crew of demons, gods, and lesser spirits, she sets out to awaken the sleeping Sea God and save her homeland and family from deadly storms.